UPAYA PENINGKATAN DIPLOMASI PUBLIK INDONESIA DI NEGARA-NEGARA ASEAN MELALUI BEASISWA SENI DAN BUDAYA INDONESIA (BSBI) - Lee Win Yew; Ludiro Madu (Jurnal Studi Diplomasi dan Keamanan, 2018)
This paper analyzes how Indonesian Art and Culture Scholarship (IACS) becomesan instrument to improve Indonesian public diplomacy in ASEAN. The Ministry of Foreign Affairs of the Republic of Indonesia has organized the IACSprogram since 2003. Starting from the ASEAN Community’s ratificationprogram in 2015, Indonesia must adjust its public diplomacy in ASEANregion. This paper applies concept of public diplomacy to look atvariousefforts to improve Indonesian public diplomacy in ASEAN and national interest to analyze why Indonesia uses public diplomacy in achieving Indonesia's national interests. By organizing the IACSprogram, Indonesia has purposeto introducing Indonesian art and culture to the people of ASEAN countries so that it can improve its public diplomacy and encounternew challenges from the ASEAN Community.